Emotional Training and Modification of Disruptive Behaviors through Computer-Game-Based Music Therapy in Secondary Education - Chao-Fernández, Rocío; Gisbert-Caudeli, Vicenta; Vázquez-Sánchez, Ruben (Applied Sciences, 2020)
Music education research has shown interest in music therapy for integral development of the person, both in their performance and academic knowledge and in their personality. This project aims to analyze the benefits of music therapy in the comprehensive training of students with disruptive behaviors (n = 6). Tests designed by Gallego, Alonso, Cruz, and Lizama (1999) were conducted to assess emotional intelligence, which showed very low results. A series of activities were designed based on the use of the music videogame Musichao, the curricular content of which was adapted for this pilot experience. Subsequently, the emotional intelligence tests were applied again to determine the effectiveness of the teaching experience. The results indicate that, with the use of this videogame, significant improvements were obtained, both in the development of multiple intelligences and in self-motivation, self-awareness, self-control, and more specifically, in social skills, minimizing behaviors that were classified as inappropriate and/or aggressive, and becoming more skilled in their interactions with the surrounding environment.
Keywords: music therapy; music games; computer game; disruptive behavior; emotional intelligence; social skills; secondary education; Scopus; JCR